Exploring Mitochondrial Evolutionary Pathways: Insights into the Origin of the Endemic Ohrid Trout - Anila Hoda; Chiara Locci; Ilenia Azzena; Noemi Pascale; Ilaria Deplano; Roland Kristo; Arian Demiri; Fabio Scarpa; Marco Casu; Daria Sanna (Life)
The Ohrid trout, Salmo letnica, is an endemic species of Lake Ohrid, one of Europe’s oldest lakes, located on the Albania-North Macedonia border. This species exhibits distinct morphotypes—Salmo letnica typicus, Salmo letnica aestivalis, Salmo letnica balcanicus, and Salmo letnica lumi—that differ in morphology and spawning behaviour. However, the extent of their genetic differentiation remains unclear. This study aimed to investigate the genetic variability and population structure of Salmo letnica morphotypes using the mitochondrial Control Region as molecular marker. We obtained 127 sequences from Salmo letnica morphotypes and compared them with sequences from other species within the genus Salmo. Phylogenetic and clustering analyses revealed no significant genetic structuring among the four morphotypes, suggesting an ecological differentiation not (yet) fixed at mitochondrial level. Additionally, our findings suggest that the modern Salmo letnica population likely originated in Lake Ohrid from Salmo farioides founders through evolutionary differentiation, potentially driven by environmental changes. Future studies incorporating a larger number of samples from both Salmo letnica and Salmo farioides are essential to fully understand the evolutionary and ecological dynamics of Salmo letnica morphotypes.